2019
DOI: 10.1039/c8cy01885e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical insights into the oxidative cleavage of resveratrol catalyzed by dioxygenase NOV1 from Novosphingobium aromaticivorans: confirmation of dioxygenase mechanism by QM/MM calculations

Abstract: QM/MM calculations confirm that the oxidative cleavage of resveratrol catalyzed by dioxygenase NOV1 follows the dioxygenase mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…9). In the study by Bai et al, the initial reactive species was identified as an end-on Fe III -O 2 − complex with a triplet or quintet spin state [77]. The lowest energy barrier reaction pathway involved attack of the activated oxygen on the α-carbon of resveratrol to generate a resonance-stabilized free radical involving the 4'-hydroxyl group.…”
Section: Computational Studiesmentioning
confidence: 99%
“…9). In the study by Bai et al, the initial reactive species was identified as an end-on Fe III -O 2 − complex with a triplet or quintet spin state [77]. The lowest energy barrier reaction pathway involved attack of the activated oxygen on the α-carbon of resveratrol to generate a resonance-stabilized free radical involving the 4'-hydroxyl group.…”
Section: Computational Studiesmentioning
confidence: 99%
“…However, the β,β-carotenoid-cleaving enzyme BCO2 also has conserved Phe residues at these positions, indicating that other factors also determine whether bicyclic carotenoids are accepted or excluded. The scissile bond is oriented with respect to the metal center such that an end-on bound O 2 molecule, modeled as suggested from computational studies (49,50), would be well aligned with the C14′-C13′ bond for dioxetane formation (Fig. 7 A and B).…”
Section: Distribution Of Ccds In Archaeamentioning
confidence: 98%
“…Dissociation of the aquo ligand may be promoted by its close interaction with the apocarotenoid. III, The aquo ligand is replaced by O 2 , with simultaneous electron transfer from the apocarotenoid to the iron-oxy complex, an intermediate suggested by computational studies(49,50). The negative surface potential (red color) may help to stabilize the cationic intermediate formed during this step.…”
mentioning
confidence: 99%
“…323 Three other CAOs functioning as stilbene cleavage oxygenases (SCOs) have recently been functionally characterized from Aspergillus fumigatus, Chaetomium globosum and Botryotinia fuckeliana 324 as well as a resveratrol cleaving dioxygenase NOV1 from Novosphingobium aromaticivorans. 325,326 Insert Figure 10 Many degradation pathways of stilbene phytoalexins have been described in fungi involving deglucosylation, dimerization and oxidation reactions leading to lactones or aldehydes. It is thus difficult to draw conclusions as to define a general mechanism for stilbene catabolism in fungi.…”
Section: Fungal Catabolism Of Stilbenesmentioning
confidence: 99%